RASHOMON DAN PEREMPUAN TUA DALAM RASHOMON: ISU PLAGIARISME - Fatoni, Akhmad (Universitas Negeri Surabaya, 2015)
Plagiarism is an immoral act in the world of authorship. But the extent to which the boundaries of a writing is called plagiarism or nonplagiat, that is what until it has not been given a benchmark. Speaking of plagiarism necessarily belongs to the originality of a writing, but when speaking of originality is certainly something that is impossible to do. For every writing must be the ideas of others in it. In the world of Indonesian literature, the issue of plagiarism has often occurred and is expressed. The incident a few years ago re-emerged in newspaper literature, precisely in the year 2011 ago. The case happened to a young writer, Dadang Ari Murtono (DAM), on the accusation that the short story in Rashomon Old Woman is a plagiarism of Rashomon's short story by Rynosuke Akutagawa, Japanese cerpenis. This paper examines the case of such plagiarism using the method of comparative literature study and using the theory of postmodernism. The purpose of this study is to uncover whether or not the DAMs act of plagiarism or the phenomenon is only political literature. In addition, it also opens up a new discourse that forms of writing as do DAM included in the category of theft or a new offer in the world of authorship.